Proceso de atención de enfermería en gestantes atendidas en un hospital de El Oro Ecuador - Lasluisa Rivera, Jessica Paola; Chantong Cabrera, Jamileth Selena; Romero Encalada, Irlandia Deifilia (My University, 2021)
The present work is based on the analysis of the statistical information of pregnant women who attended the hospital of El Oro Ecuador, The objective of this work is to elaborate nursing care plans related to the main complications that the pregnant women attended in a hospital of The Gold Ecuador. This research is cross-sectional, analytical and investigative, related to the nursing care process according to the main complications that pregnant women presented, whose results show that 21.38% of pregnant women are adolescents, which constitutes risk pregnancies, the rate of Caesarean sections of this institution is 20.8%, considered high since according to the World Health Organization (WHO) the adequate figures are 10 to 15%.
El presente trabajo, está basado en el análisis de la información estadística de gestantes que acudieron al hospital de El Oro Ecuador, El objetivo de este trabajo es elaborar planes de cuidado de Enfermería relacionados a las principales complicaciones que presentaron las gestantes atendidas en un hospital de El Oro Ecuador. Esta investigación es de tipo transversal, analítico e investigativo, relacionado con el proceso de atención de enfermería según las principales complicaciones que presentaron las gestantes, cuyos resultados muestran que el 21.38% de gestantes son adolescentes, lo que constituye embarazos de riesgo, la tasa de cesáreas de esta institución es del 20.8 %, considerada alta ya que según la Organización Mundial de la Salud (OMS) las cifras adecuadas son de 10 al 15%.
Keywords: PROCESO DE ATENCION DE ENFERMERIA; PARTO VAGINAL; CESAREA; SHOCK HIPOVOLEMICO.